Enantioselective Epoxidation of Non-conjugated cis-Olefins by Chiral Dioxirane - Burke, Christopher P. (2009)
[Image: see text] A variety of non-conjugated cis-olefins has been enantioselectively epoxidized with chiral ketones 2, and up to 92% ee has been obtained. The two prochiral faces of an olefin are likely stereodifferentiated by the relative hydrophobicity of the olefin substituents and/or allylic oxygen functionality.